El manejo de archivo en el GAD municipal de chambo y su incidencia en la imagen institucional, período enero a julio de 2014. - León Zavala, Flor Silvana (2016)
The work entitled: Managing file in the Municipal GAD Chambo and its impact on corporate image, period January to July 2014, had as its main purpose to establish how the archiving process is carried out in the different departments of the company and how affects the formation of the image the internal and external public has about the institution. To achieve this purpose theoretical information of the variables that served as a basis for the research was collected. The opinion of internal and external audiences was obtained through the application of surveys designed for each group and their results are presented in statistical tables and charts accompanied with the respective analysis and interpretation, comparing the theoretical bases with the characteristics of the study and proceeding testing the hypothesis that showed how file management affects the institutional image. Starting from the main detected falencia regard to training needs, the proposal to maintain a process of training for those responsible for the management of departmental and institutional file is developed, as it is considered that an efficient management and quality contribute to the forming a positive image in customers Chambo Municipal GAD.